Fatigue crack growth rates for offshore wind monopile weldments in air and seawater: SLIC inter-laboratory test results - Mehmanparast, Ali; Brennan, Feargal P.; Tavares, Isaac (Elsevier, 2016)
The majority of fatigue crack growth (FCG) data sets available on steels in air and seawater environments are several decades old and may not be appropriate for structural integrity assessment of offshore wind turbine foundations, which are fabricated using contemporary materials and welding technologies. Therefore, the SLIC joint industry project was formed to investigate the fatigue crack initiation and growth behaviour in offshore wind welded steel foundations. The FCG test data from the SLIC inter-laboratory (round robin) test programme have been analysed using a new proposed shape function solution and the results are presented and discussed. The obtained FCG trends in air and seawater environments have been compared with the recommended trends available in standards. The Paris-law constants and ΔKth values obtained from this programme can be used for defect assessment and remaining life prediction of offshore monopile weldments in air and seawater environments. The results from the SLIC project show that for a given value of ΔK the fatigue crack growth rate, da/dN, is on average around 2 times higher in seawater compared to air for the base metal and weldments. This factor of 2 in the seawater environment is almost half of the crack acceleration factor recommended by standards.
Keywords: Fatigue crack growth; Monopile; Weldments; Offshore wind; HAZ; Base metal